Drama and resistance : bodies, goods, and theatricality in late medieval England - Sponsler, Claire (Medieval cultures, 1997)
Claire Sponsler explores the intertwined histories of bodily subjectivity, commodity culture, and theatricality in late medieval England. In a fascinating consideration of popular drama in the period from 1350 to 1520, she argues that many types of performances during this time represented cultural evasions of the imposition of disciplinary power.